Pregabalin Abuse in between Jordanian youths need to concern - A. Obiesat, Dr. Maxim; Marashdeh, Dr. Muath F.; K Al-Zoubi, Dr. Arafat; M. Al-Alwan, Dr. Malik; Al-Odat, Dr. Raya T. (International Journal of Scientific Research and Management (IJSRM), 2019)
Pregabalin is a medication used extensively in neurosurgery and mental health care as it is sometimes used in primary health care in medical conditions but is increasingly reported as a potential increase of use leads to misuse and abuse. The fact, increase both levels of abuse and death; along with the growing non-medical use through black market have been reported in Jordan.